2018
DOI: 10.1159/000492988
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-138 Aggravates Inflammatory Responses of Macrophages by Targeting SIRT1 and Regulating the NF-κB and AKT Pathways

Abstract: Background/Aims: With increased understanding of sepsis, mortality is decreasing. However, there is still a lack of effective therapeutic strategy. The inflammatory response of macrophages is critical during sepsis. Methods: Macrophages were stimulated with LPS. Western blotting and qRT-PCR were used to detect inflammatory responses. Then, the inhibitor of microRNA-138 was transfected and Western blotting, qRT-PCR, H&E staining and ELISA were used to verify the role of microRNA-138 in inflammation. Then target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(44 reference statements)
1
10
0
1
Order By: Relevance
“…C57BL/6 mice were intraperitoneally injected with LPS (10 mg/kg; Sigma-Aldrich; Merck KGaA) to induce sepsis. For treatment, the inhibitor control (80 mg/kg/day; 5'-CAG UAC UUU UGU GUA GUA CAA-3'; Shanghai GenePharma Co., Ltd.), miR-15a-5p inhibitor (80 mg/kg/day; Guangzhou RiboBio Co., Ltd.) or miR-15a-5p inhibitor (80 mg/kg/day; 5'-CAC UGG UAC AAG GGU UGG GAG A-3'; Shanghai GenePharma Co., Ltd.) + TNIP2-siRNA (80 mg/kg/day) were injected by caudal vein for 3 consecutive days as previously described (30), followed by LPS (10 mg/kg) injection at 24 h following the last administration. The mice were anaesthetized with sodium pentobarbital (30 mg/kg; intraperitoneal injection) and sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were intraperitoneally injected with LPS (10 mg/kg; Sigma-Aldrich; Merck KGaA) to induce sepsis. For treatment, the inhibitor control (80 mg/kg/day; 5'-CAG UAC UUU UGU GUA GUA CAA-3'; Shanghai GenePharma Co., Ltd.), miR-15a-5p inhibitor (80 mg/kg/day; Guangzhou RiboBio Co., Ltd.) or miR-15a-5p inhibitor (80 mg/kg/day; 5'-CAC UGG UAC AAG GGU UGG GAG A-3'; Shanghai GenePharma Co., Ltd.) + TNIP2-siRNA (80 mg/kg/day) were injected by caudal vein for 3 consecutive days as previously described (30), followed by LPS (10 mg/kg) injection at 24 h following the last administration. The mice were anaesthetized with sodium pentobarbital (30 mg/kg; intraperitoneal injection) and sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…16 Additionally, recent studies elucidated that several other miRNAs regulated the inammatory responses of macrophages through targeting SIRT1, such as miR-138 and miR-199a. 36,37 In conclusion, our data indicated that miR-486 expression was elevated in serum of sepsis patients and LPS-stimulated macrophages. Furthermore, miR-486 silencing alleviated the inammatory response at least partly through targeting SIRT1 in LPS-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 57%
“…In 2013, Gong et al noted that inhibition of miR-138 induced lipid raft formation by constitutive NF-kB activation and upregulating many components of lipid rafts (Gong et al, 2013). Even though SIRT1 has been found as a potential target of miRNA-138 in macrophages, smooth muscle cells, endothelial cells, and tumor cells, no data has been published in PCa concerning miR-138 and SIRT1 expression (Xu et al, 2015;Zhu et al, 2017;Bai et al, 2018). In current study, our results showed that miR-138-5p could specifically bind the 3′UTR region of SIRT1 and inhibit the expression of SIRT1 in PCa cells.…”
Section: Discussionmentioning
confidence: 99%